Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes

Molecular investigation of glycated insulin-induced insulin resistance via insulin signaling and AGE-RAGE axis - Walke, Prachi B.; Bansode, Sneha B.; More, Nikita P.; Chaurasiya, Arvindkumar H.; Joshi, Rakesh S.; Kulkarni, Mahesh J. (Biochimica ET Biophysica Acta-Molecular Basis of Disease, 2021)
Hyperglycemic condition in diabetes promotes glycation of various plasma proteins including insulin. Glycation of insulin has been reported to reduce its biological activity. Reduced biological activity of glycated insulin could be either due to reduced affinity for the insulin receptor and impaired insulin signaling, or it can act as a ligand for the receptor for advanced glycation end products (RAGE) and activates oxidative stress and pro-inflammatory pathways leading to insulin resistance. This study investigates the effect of glycated insulin on both insulin and RAGE signaling. Glycated insulin treatment to Chinese hamster ovary (CHO-IR-GLUT4) cells stably expressing insulin receptor (IR) and glucose transporter fused with a green fluorescent protein (GLUT4-GFP) resulted in the impairment of insulin signaling, as the phosphorylation of IR and AKT significantly reduced, which affected GLUT4 translocation and glucose uptake. Moreover, it also activated RAGE signaling as observed by increased expression of NADPH oxidase accompanied by an increase in reactive oxygen species (ROS). Immunofluorescence study indicated the translocation of NF-kappa B to the nucleus upon treatment of glycated insulin. This was associated with increased RAGE expression, Caspase 3, and cell death. Downregulation of RAGE with the losartan treatment restored the impaired insulin signaling and glucose uptake. Additionally, in silico study demonstrated that glycated insulin has reduced binding affinity to insulin receptor and increased binding affinity to RAGE. Overall, this study demonstrates the role of glycated insulin in exacerbating insulin resistance by impairing insulin signaling as well as stimulating AGE-RAGE signaling.
Keywords: AGE; Diabetes; Glycation; Hyperglycemia; insulin; RAGE